Estimation of greenhouse gas emissions in the agro-industrial system of sugarcane in Piauí, Brazil - Pinto, Lilian de Castro Moraes (Ciência e Natura, 2019)
The present study presents an estimate of greenhouse gas emissions throughout the production process of ethanol and sugar originated from sugarcane in Piauí. The field research was carried out in a mill with an attached distillery, where the harvest was conducted manually, from January to December 2015. Life Cycle Assessment principles were considered in the quantification of total CO2, CH4 and N2O emissions in the stages of agriculture, industrialization and distribution, converting them according to their global-warming potential into carbon-equivalent (CO2eq). The use of fuels, agriculture inputs, sugarcane burning, manufacture of machinery and physical structure of the mill, application of pesticides, seeds, use of chemical reagents in the production process and human labor were considered in this study. The results show a total emission of 2,413.3 kg CO2eq /ha.year, and the main key sources were sugarcane burning (48%) and use of chemical products (29.6 %). The industrial and distribution stages contributed with 2% of the emissions each. There was an emission of 29.9 kg CO2eq per ton of sugarcane processed and it was estimated that there would be a net reduction of 83% of emissions if the harvesting could be thoroughly conducted mechanically.